Investigating key factors influencing the success of construction projects at international level - Büşra Göküz; İlknur Akıner (Discover Civil Engineering)
Abstract The construction sector is an important area of activity that contributes greatly to economic growth. However, the increasing scale and complexity of international construction projects requires a comprehensive strategy to achieve success. In this context, identifying the key factors that affect success in construction projects is critical to overcoming the challenges faced by the sector and to carrying out projects more efficiently. The main purpose of this study is to identify the critical success factors affecting success in international construction projects and to analyze the effects of these factors on project success. The research aims to classify these factors and evaluate their importance levels. The research was conducted using a systematic literature review method. Using the PRISMA method, 32 articles obtained from the searches conducted with the keywords "construction projects" and "project success" were examined and eight publications focusing on critical success factors were included in the detailed analysis from these studies. In addition, a correlation matrix was used to determine the relationship between the variables. As a result of the analysis, the main factors affecting project success were determined as project management skills, technical competence, clear and realistic goals, contract management and motivation. In addition, it was observed that factors such as lack of human resources and subcontractor coverage negatively affected the project. The strong positive and negative relationships between the factors were discussed in detail in the research. It was observed that project management skills and technical competence were prominent among the factors determining success in international construction projects. The success rate of projects where motivation is high, clear goals are determined, and effective contract management is implemented increases significantly. The research highlights the impact of considering these factors together on project success.